Youth labor market interventions - Jochen Kluve (IZA World of Labor, 2014)
Reducing youth unemployment and generating more and better youth employment opportunities are key policy challenges worldwide. Active labor market programs for disadvantaged youth may be an effective tool in such cases, but the results have often been disappointing in Organisation for Economic Co-operation and Development (OECD) countries. The key to a successful youth intervention program is comprehensiveness, comprising multiple targeted components, including job-search assistance, counseling, training, and placement services. Such programs can be expensive, however, which underscores the need to focus on education policy and earlier interventions in the education system.
Keywords: M53; J64; I25; 330; active labor market programs; youth unemployment; training